XMD-17-51 Inhibits DCLK1 Kinase and Prevents Lung Cancer Progression - Yang, Wei-Qiang; Zhao, Wei-Jun; Zhu, Liu-Lian; Xu, Shuai-Jun; Zhang, Xue-Lin; Liang, Yong; Ding, Xiao-Fei; Kiselyov, Alexander; Chen, Guang (Frontiers in Pharmacology, 2021)
Abstract Doublecortin-like kinase 1 (DCLK1) is a cancer stem cell (CSC) marker that is highly expressed in various types of human cancer, and a protein kinase target for cancer therapy that is attracting increasing interest. However, no drug candidates targeting DCLK1 kinase have been developed in clinical trials to date. XMD-17-51 was found herein to possess DCLK1 kinase inhibitory activities by cell-free enzymatic assay. In non-small cell lung carcinoma (NSCLC) cells, XMD-17-51 inhibited DCLK1 and cell proliferation, while DCLK1 overexpression impaired the anti-proliferative activity of XMD-17-51 in A549 cell lines. Consequently, XMD-17-51 decreased Snail-1 and zinc-finger-enhancer binding protein 1 protein levels, but increased those of E-cadherin, indicating that XMD-17-51 reduces epithelial-mesenchymal transition (EMT). Furthermore, sphere formation efficiency was significantly decreased upon XMD-17-51 treatment, and XMD-17-51 reduced the expression of stemness markers such as β-catenin, and pluripotency factors such as SOX2, NANOG and OCT4. However, the percentage of ALDH+ cells was increased significantly following treatment with XMD-17-51 in A549 cells, possibly due to EMT inhibition. In combination, the present data indicated that XMD-17-51 inhibited DCLK1 kinase activity in a cell-free assay with an IC50 of 14.64 nM, and decreased DCLK1 protein levels, cell proliferation, EMT and stemness in NSCLC cell lines. XMD-17-51 has the potential to be a candidate drug for lung cancer therapy.